Respuesta :

Answer:

2q+6

Step-by-step explanation:

So basically, you would do this.

-2q-6+6q+12-2q

Next

-4q+6q = 2q

12-6=6

2q+6

Answer:

2q + 6

Step-by-step explanation:

To simplify, we will use the distributive property.

-(2q + 6) simplifies to -2q - 6 (In this case we are distributing the - sign or -1)

3(2q + 4) simplifies to 6q + 12

So if we recombine: -2q - 6 + 6q + 12 - 2q

Let's combine like terms (q's with q's, numbers with numbers)

-2q + -2q + 6q = 2q

-6 + 12 = 6

So if we recombine: 2q + 6